ESCOLHA DOS GESTORES ESCOLARES: UM ESTUDO NA REDE PÚBLICA MUNICIPAL DE IMPERATRIZ - MA - MOTA, Paula Alexandra T (2022)
This dissertation aimed to analyze the process of choice of school managers in the municipal school system of Imperatriz-MA and its impacts on the democratic management of schools. And, more specifically, to know and analyze the regulatory instruments for the choice of school manager, to verify the various alternatives for choice, how this choice impacts on the democratic management of public schools, as well as to understand whether the choice of this manager contributes to the construction of democratic school practices. The object in focus is inserted in a broad context, which involves historical, social, political and economic aspects that determine the ways of filling the position of school manager. As to the technical procedures, we used bibliographic and documental research and field research. The instruments used were semi-structured interviews with the principals, the president of the Municipal Board of Education, and representatives of parents, students, teachers, employees, and the local community in two schools of the municipal educational system. As a work product, a guidance booklet was presented. The results of the study showed that the democratization of public school management, although it has been guaranteed through regulatory frameworks implemented in schools, is still a long way from being considered democratic. The study also showed that even though the manager is chosen through elections, a mechanism that should ensure participatory and democratic management, there are still some obstacles that hinder the implementation of democratic practices in schools. One of them is the authoritarianism exercised by the manager, who centralizes the power, not allowing the involvement of the community in the decision-making process; another is the lack of knowledge by the school community about its role within the school.